NILAI KETUHANAN YANG MAHA ESA DALAM PEMBENTUKAN KARAKTER PELAJAR PANCASILA DI SEKOLAH MENENGAH PERTAMA - Sibaweh, Imam; Asep Abdullah; Aan Hasanah; Bambang Samsul Arifin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The Implementation of the Divine Values in Shaping the Character of Pancasila Students at Junior High School. This study aims to investigate the implementation of the value of the Almighty God in shaping the character of Pancasila students at Diponegoro Junior High School in Tumpang. In the context of Indonesia, Pancasila serves not only as the philosophical foundation of the state but also as a framework in education for shaping the character of the younger generation. However, despite Pancasila being formally integrated into the curriculum, the implementation of religious values, including the value of the Almighty God, often encounters challenges in practice. The research method employed is a qualitative approach with a case study design. Data were collected through participatory observation, in-depth interviews, and document analysis. The findings indicate variations in the implementation of religious values among the schools under study, with challenges primarily related to teachers' understanding and commitment, as well as resource availability. Nonetheless, the study also identifies positive efforts made by some schools to address these challenges. Overall, the research emphasizes the importance of teachers' role, collaboration between schools and religious communities, and the development of value-oriented learning approaches to enhance the formation of students' character based on religious values in Indonesia. Keywords: Implementation; Divinity Values; Character Formation;